2013
DOI: 10.1080/19338244.2011.646361
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Effects Among Rubberwood Furniture Factory Workers in Thailand

Abstract: Respiratory symptoms and pulmonary function were examined among 89 rubberwood furniture factory workers. Acute and chronic irritant symptoms were assessed, lung function was measured both pre- and post-shift and personal inhalable dust exposure determined. The only symptoms with a significant increase among high dust level-exposed workers (>1 mg/m(3)) were those related to nasal irritation. High dust level-exposed workers had a significant cross-shift decrease in forced expiratory volume in 1 second/forced vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
2
1
0
4
Order By: Relevance
“…The results from this study of Para rubber wood sawmills in southern Thailand demonstrated that the workers in sawmills were exposed to wood dust and noise above permissible exposure limits, especially in process of sawing the lumber into sheets, and planing and re-arranging, respectively ( Table 4 and 5 ) . The dust level measurements were similar to previous studies of dust exposure to processing of Para rubber tree lumber 14,15) . It should be noted, however, that these previous studies were conducted at the Para rubber furniture factories, not sawmills.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results from this study of Para rubber wood sawmills in southern Thailand demonstrated that the workers in sawmills were exposed to wood dust and noise above permissible exposure limits, especially in process of sawing the lumber into sheets, and planing and re-arranging, respectively ( Table 4 and 5 ) . The dust level measurements were similar to previous studies of dust exposure to processing of Para rubber tree lumber 14,15) . It should be noted, however, that these previous studies were conducted at the Para rubber furniture factories, not sawmills.…”
Section: Discussionsupporting
confidence: 86%
“…We used JSA, hazard identification, risk assessment, and what if analysis 13) .J S A methodology was adapted from Job Hazard Analysis, OSHA Publication 3071 18) . Risk levels were assessed using the following steps: 1) an operational issue or occupational health problem was identified during inspection, reported and recorded, which required the attention of occupational safety personnel and the managers of each factory; 2) the researchers and occupational safety personnel Acceptable risk; Need to review working procedure and control of hazard [8][9][10][11] High risk; Needs to manage and control [12][13][14][15][16] No acceptable risk or tolerance; Need to stop and provide a control method or procedure in order to restart a Total score calculated by multiplying "chance of occupational health event" by "severity of occupational health event"…”
Section: Measuring and Calculating Risk Levelsmentioning
confidence: 99%
“…Na realização das provas de função respiratória é frequente encontrar diminuição de alguns parâmetros 4,8,11,12,13 , sobretudo nos profissionais mais expostos 4, 11 e à medida que o turno progride 11 . A diminuição da capacidade pulmonar associa-se à irritação mecânica e/ ou química do tecido pulmonar, tendo como consequência a diminuição do calibre das vias respiratórias e diminuição da concentração de oxigénio.…”
Section: Partículas Derivadas Da Madeiraunclassified
“…Alguns investigadores defendem a possibilidade de existir reatividade cruzada entre os diversos alérgenos 3 . A semiologia mais frequente é caraterizada por irritação ocular (prurido-"comichão" e eritema-"vermelhidão") 8 , obstrução nasal a alternar com rinorreia (fluxo nasal) 6,8 , irritação da mucosa nasal 3,4,6,11 , espirros, tosse e dispneia (dificuldade respiratória). A alergia secundária ao contato com a madeira associa-se não só aos constituintes desta, mas também aos produtos químicos 6,13 e eventuais agentes biológicos presentes 6 .…”
Section: Partículas Derivadas Da Madeiraunclassified
See 1 more Smart Citation